FUNGSI TASAWUF TERHADAP PEMBENTUKAN AKHLAK (ETIKA) KERJA:Studi pada Murid Tarekat Qadiriyah Naqsyabandiyah di Kota Pontianak Kalimantan Barat - Fatmawati Fatmawati (Jurnal Theologia, 2013)
Abstract: Every adult male who works with various types of background work is a form of responsibility to provide for his family members . Observing one's work activities , this study analyzed the work activities on college institutes followers of Qadiriyah Naqsyabandiyah (QN) in Pontianak city. The research analyzes using perspective of Sociology of Religion , how functions can Sufism moral formation (ethics ) working his followers . Furthermore, this study used a qualitative approach comes with a descriptive method. Networking research data using the snowball technique in college institutes informant followers of Qadiriyah Naqsyabandiyah As-Salam and An-Nuur in Pontianak city QN flow assuming a more dominant in Pontianak. The next stage of data were analyzed using qualitative analysis. The results of the research—stageportrait of detainees practice Sufism by iḥsān; students were guided by mursyid (teacher like procession allegiance) and remembrance procession done consistently implications for morality (ethics) work has a spiritual dimension and Islamic values. Morality (ethics) refers to the working properties such as the nature of the Prophet Muhammad,ṣiddiq (right ), amanah (trust), faṭanah (intelligence) and tablīgh (sermons/promotion) which is still relevant today. When performing work activities of Qadiriyah Naqsyabandiyah (QN)followersfeel have the power within themselves so that they always feel to be watched. They are careful in their work and always maintain appropriate behavior Islamic morality . Abstrak: Setiap laki-laki dewasa yang bekerja dengan berbagai latar belakang jenis pekerjaan adalah sebagai bentuk tanggung jawabnya untuk memberi nafkah anggota keluarga¬nya. Mencermati aktivitas kerja seseorang, kajian ini meng¬analisis aktivitas kerja pada pengikut perguruan tarekat Qadiriyah Naqsyabandiyah (QN) di kota Pontianak. Adapun pisau analisis penelitian menggunakan persfektif Sosiologi Agama, bagimana fungsi tasawuf dapat pembentukan akhlak (etika) kerja para pengikutnya. Selanjutnya penelitian ini menggunakan pendekatan kualitatif dilengkapi dengan metode deskriptif. Penjaringan data penelitian ini meng¬gunakan teknik snow ball yakni pada informan pengikut perguruan tarekat Qadiriyah Naqsyabandiyah As-Salam dan An-Nuur di kota Pontianak dengan asumsi aliran QN lebih dominan di Pontianak. Tahapan selanjutnya data dianalisis dengan menggunakan analisis kualitatif. Hasil penelitian mengambarkan tahapan-tahahan pengamalan tasawuf oleh ikhsan/murid yang dibimbing oleh mursyid/guru seperti prosesi bai’at (ikrar) dan prosesi zikir yang dilakukan secara konsisten berimplikasi pada akhlak (etika) kerja yang mempunyai dimensi spiritual dan nilai-nilai Islami. Akhlak (etika) kerja merujuk sifat-sifat Nabi Muhammad Saw seperti sifat ṣiddiq(benar), amanah (tangungjawab), faṭanah (kecerdasan) dan tablīgh (promosi) yang masih relevan hingga kini. Ketika melakukan aktivitas kerja para pengikut QN merasa mempunyai kekuatan spiritualdi dalam dirinya, yakni merasa selalu ada yang mengawasi. Mereka berhati-hati dalam bekerja dan selalu menjaga perilakunya sesuai akhlak Islami. Keywords: tasawuf, tarekat, akhlak, etika.